Empowering Deaf Youth Through Vocational Training: Case Study of Participants Balai Rehabilitasi Sosial Penyandang Disabilitas Sensorik Rungu Wicara Melati Social Ministry of The Republic Indonesia - Aisha Nadya; Acmad Ali Syaifudin; Irfan Fahriza (Study Program Guidance and Counseling, Univesitas Pendidik, 2022)
Marginalized people are typically at risk of undesirable outcomes and experiences. Youth, especially those who the deaf, face significant challenges in making the transition from school to career life. Vocational Training is organized by the Ministry of Social Affairs of the Republic of Indonesia to equip deaf youth with skills that suit their interests and talents. Empowerment can be understood as acknowledging or empowering oneself, gaining or regaining the power, energy, and imagination to structure one's situation. This research uses a qualitative research approach with a case study with as many as four deaf people as informants who have carried out a vocational training program located at Balai Melati. Methods of data collection in studies using depth interviews. Data validity was tested using source triangulation and member-checking methods. Furthermore, the data analysis techniques were interactive models consisting of data reduction, data display, and conclusion. The results of this study show that vocational training can be a means of empowerment for deaf individuals. There are barriers to female informants. Without proper support, deaf women cannot contribute effectively to their communities' societies and economies. Within the deaf community, parental hearing status plays an important role. Due to the negative stigma attached to deaf individuals, it is recommended that guidance and counseling services be provided in vocational training programs